Prognostic value of the ubiquitin ligase carboxyl terminus of the Hsc70‐interacting protein in postmenopausal breast cancer. (23rd June 2016) - Kurozumi, Sasagu; Yamaguchi, Yuri; Hayashi, Shin‐ichi; Hiyoshi, Hiromi; Suda, Tetsuji; Gohno, Tatsuyuki; Matsumoto, Hiroshi; Takei, Hiroyuki; Horiguchi, Jun; Takeyoshi, Izumi; Oyama, Tetsunari; Kurosumi, Masafumi
Abstract: The carboxyl terminus of the Hsc70‐interacting protein (CHIP) is considered to induce the ubiquitination and degradation of several oncogenic proteins, and play a role in the inhibition of tumor progression and invasion under experimental conditions. However, the impact of CHIP expression on the prognosis of breast cancer patients has not yet been established. In this study, using an immunohistochemical method, 272 patients with invasive breast cancer were assessed for the expression of CHIP (graded scores 0‐3) and the statuses of biomarkers, such as estrogen receptor (ER), progesterone receptor (PgR), and HER2. The relationships between the statuses of CHIP and biomarkers as well as clinical features were also evaluated, and that between the expression of CHIP and patient prognosis was analyzed. We revealed that the strong expression of CHIP correlated with positive ER ( P < 0.001), positive PgR ( P < 0.001), and negative HER2 ( P = 0.02). In postmenopausal patients, relapse‐free survival (RFS) was significantly better in the high CHIP group than in the low CHIP group ( P = 0.042). In addition, RFS and cancer‐specific survival (CSS) were significantly better in patients with ER‐positive/CHIP score 3 tumors than in those with ER‐negative/CHIP score 0 tumors (RFS: P = 0.038, CSS: P = 0.0098). The methylation status of CHIP gene promoter did not always account for the down‐regulation of its expression. In conclusion, the overexpression of CHIP is a potent prognostic factor of a good prognosis in ER‐positive breast cancer patients in the postmenopausal phase. Abstract : In our study, we identified the expression of CHIP as a potent prognostic factor in postmenopausal patients with invasive breast cancer. Among postmenopausal ER‐positive patients, survival rates were better in the high CHIP group than in the low CHIP group.